Model Pemberdayaan Masyarakat Kolaboratif Berbasis Participatory Action Research (PAR): Sinergi Revitalisasi Spiritualitas Keagamaan dan Penguatan Ekonomi Lokal di Dusun Carabaka, Bawean. - Rahel, Muhammad; Muhammad Ali; Eliyana; Maqtuatis Surrah; Ummu Habibah; Rafi'atul Aliyah; Darmawan; Maulidah (LP3M IAIFA Kediri, 2025)
The village of Carabaka on Bawean Island is faced with two challenges: revitalizing its social and religious spirit, and optimizing its untapped local economic potential. Often, the separation between spiritual activities and economic growth hinders holistic community development. Therefore, this community service program aims to implement a collaborative community empowerment model that synergizes the revitalization of religious spirituality with strengthening the local economy. The program uses Participatory Action Research (PAR), in which the community is involved in every stage of the process, from planning and action to observation and reflection. This strategy is realized through programs such as fundraising for mosque renovations, supporting home-based chip businesses, and strengthening religious educational institutions. The results of the community service program demonstrate that this collaborative model successfully creates strong synergy. Community participation in religious activities has increased, building social capital in the form of trust and mutual cooperation. This social capital then serves as the foundation for economic mentoring programs, as evidenced by the growth of local chip businesses. Thus, the PAR approach has proven effective in uniting the two key pillars of sustainable village development.